2012
DOI: 10.1063/1.3698408
|View full text |Cite
|
Sign up to set email alerts
|

Langevin dynamics simulation of polymer-assisted virus-like assembly

Abstract: Starting from a coarse grained representation of the building units of the minute virus of mice and a flexible polyelectrolyte molecule, we have explored the mechanism of assembly into icosahedral structures with the help of Langevin dynamics simulations and the parallel tempering technique. Regular icosahedra with appropriate symmetry form only in a narrow range of temperature and polymer length. Within this region of parameters where successful assembly would proceed, we have systematically investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 51 publications
5
74
0
Order By: Relevance
“…The result of sequence-independent genome packing based only on electrostatics has been observed in experiments as well. 165,172,173 Simulation studies 167,168,170 of the kinetics of virus assembly showed that the process is dominated by electrostatics and ideas from polymer crystallization can be substantively used to understand the simulation and experimental results. 174176 As one would expect, there are several additional avenues to expand the theoretical approach to address finer details of virus assemblies.…”
Section: Electrostatically Driven Structure In Polyelectrolyte Solutionsmentioning
confidence: 99%
“…The result of sequence-independent genome packing based only on electrostatics has been observed in experiments as well. 165,172,173 Simulation studies 167,168,170 of the kinetics of virus assembly showed that the process is dominated by electrostatics and ideas from polymer crystallization can be substantively used to understand the simulation and experimental results. 174176 As one would expect, there are several additional avenues to expand the theoretical approach to address finer details of virus assemblies.…”
Section: Electrostatically Driven Structure In Polyelectrolyte Solutionsmentioning
confidence: 99%
“…Several groups have therefore developed models for subunits which, although highly simplified, retain the most important features. Namely, they have an excluded-volume geometry and orientation-dependent attractions designed such that the lowest energy structure is shell with icosahedral symmetry [76, 105, 106, 112, 128, 172, 188190, 209211, 227, 272274]…”
Section: Modeling Self Assembly Dynamics and Kinetics Of Empty Cmentioning
confidence: 99%
“…12B). For example, several groups [190, 208, 210] have considered models in which subunits have a trapezoidal shape which is roughly consistent with that of capsid proteins with the beta-barrel architecture [219] or models in which 20 triangular subunits (which could correspond to protein trimers) form icosahedral shells [76, 106, 172, 188, 209, 210]. Extended subunits have also been used to model nanoparticles with a variety of shapes (e.g.…”
Section: Modeling Self Assembly Dynamics and Kinetics Of Empty Cmentioning
confidence: 99%
“…[15][16][17] With increased computing power and improved simulation techniques, it has become possible to simulate mesoscale models that reproduce such self-assembling behaviour. In recent years mesoscopic models have been used to assemble micelles, [18][19][20][21][22][23][24][25][26][27][28][29][30][31] vesicles, 29,32,33 hollow shells of specific symmetry analogous to virus capsids [34][35][36][37][38][39][40][41][42] and aggregates of particles which resemble protein clusters. 43 Additionally, reflecting the growth of DNA nanotechnology, 44 many coarse-grained models of DNA assembly have recently been proposed.…”
Section: Introductionmentioning
confidence: 99%